Developing Instruments for Employability Skills Measurement for Trainee Teachers in Technical and Vocational Education Field - Hanapi, Zaliza Binti (Journal of Technical Education and Training, 2019)
The purpose of this research is to identify the key elements of an employability skill which is important and should be mastered by trainee teachers in the field of technical and vocational education as well as to produce instruments measuring their employability skills. These instruments can also be used to identify the extent to which lecturers integrate the skills employability that is important in the student. Modified Delphi Techniques and Rasch model approach was used to examine the reliability, validity and suitability of individual items. The final instrument of employability skills measurement among trainees in technical and vocational education field has been verified which encompasses nine key elements of employability skills consists communication skills , critical and creative thinking, information management, teamwork and collaboration, self-management, professional ethics and morals, leadership, entrepreneurship and social skills and representing 81 skills items. Verily, all these elements of employability skills need to be mastered by graduates in order to produce highly qualified and competitive professionals teachers.